Estrategias didácticas lúdicas y participación de los estudiantes en el proceso de enseñanza aprendizaje de Ciencias Naturales. Año Lectivo 2023 – 2024. - Carrión Correa, Nahomi Elizabeth (2024)
During the teaching-learning process of Natural Sciences, the application of playful didactic strategies is fundamental to improve the academic performance of the students, therefore, for the present research work the following objective was proposed: To improve the academic performance of the students through the application of playful didactic strategies that allow motivating their interest and participation in the teaching-learning process of Natural Sciences, eighth year of EGB, of the School of Basic Education "Graciela Atarihuana de Cueva". Academic year 2023 - 2024. In the development of this research, the inductive method was used, starting from direct observation to identify the shortcomings of the student's learning process and the lack of application of playful didactic strategies. In addition, this research has a qualitative approach and a descriptive design was used, since it describes, records, analyzes, and interprets the events observed in the students' classroom process. The results of the research show that the explanatory-illustrative didactic strategies, gamification, active learning, autonomous learning, and situated learning are the ones that enhanced the interest, motivation, and academic performance of the students during the development of the classes. It is concluded that the ludic didactic strategies significantly improve the academic performance of the students and allow the creation of a dynamic, attractive, and interactive environment, which motivates the interest and participation of the students during the teaching and learning process of Natural Sciences. Keywords: ludic didactic strategies, teaching-learning, academic